Design and development of an English as a global language MOOC to increase global Englishes awareness : evaluation in a Thai university - Krich Rajprasit, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Global Englishes Language Teaching (GELT) framework has been proposed as a practical guidance for researchers and practitioners to reconsider and revise their current teaching practices to recognize a global status of English in multilingual communities (Galloway & Rose, 2018). However, the GELT framework still requires extensive evidence from stakeholders in the field of English language teaching. This study aims to design and evaluate an ‘English as a global language’ massive open online course or EGL-MOOC to increase awareness of Global Englishes among first-year students enroled in a general English course of a Thai university. To design and develop the EGLMOOC, contents and instructional materials (i.e., Infographics, motion graphics, video clips, reading passages, online discussion tasks, module tests) were produced based on the GELT framework. To identify the students’ Global Englishes awareness, a set of pre-and post-teaching questionnaires and student reflections were employed, together with MOOC evaluation questionnaire for determining quality of the EGL-MOOC. The findings demonstrate practical suggestions on MOOC design and implementation for Thai university students to raise their knowledge of Global Englishes after MOOC implementation in a general English course. This study also highlights innovative MOOC design and development to promote the sociolinguistic realities of English, as well as respectful attitudes towards the English diversity.